Strategies for Improving Transdermal Administration: New Approaches to Controlled Drug Release - Olimpia Dumitriu Buzia; Ana Maria Păduraru; Claudia Simona Stefan; Monica Dinu; Dorin Ioan Cocoș; Lawrence Chukwudi Nwabudike; Alin Laurențiu Tatu (MDPI AG, 2023)
In this work, we aim to address several strategies to improve transdermal drug delivery, such as iontophoresis, sonophoresis, electroporation and micron. We also propose a review of some transdermal patches and their applications in medicine. TDDs (transdermal patches with delayed active substances) are multilayered pharmaceutical preparations that may contain one or more active substances, of which, systemic absorption is achieved through intact skin. The paper also presents new approaches to the controlled release of drugs: niosomes, microemulsions, transfersomes, ethosomes, but also hybrid approaches nanoemulsions and microns. The novelty of this review lies in the presentation of strategies to improve the transdermal administration of drugs, combined with their applications in medicine, in light of pharmaceutical technological developments.